Network meta‐analysis of studies included in the Clinical Practice Guideline on the nonsurgical treatment of chronic periodontitis. (2nd June 2017) - John, Mike T.; Michalowicz, Bryan S.; Kotsakis, Georgios A.; Chu, Haitao
Abstract: Aim: The recent ADA‐commissioned Clinical Practice Guideline on the nonsurgical treatment of chronic periodontitis has provided the most exhaustive library of clinical trials on scaling and root planing (SRP) with or without adjuncts. This network meta‐analysis (NMA) compared the adjuncts against each other. Materials and Methods: A star‐shaped NMA was performed based on 36 indirect comparisons of clinical attachment‐level (CAL) gains among nine adjuncts in 74 studies from the Clinical Practice Guideline. Results: All pairwise differences were accompanied by wide confidence intervals, and none of the adjuncts were statistically significantly superior to another. Local doxycycline hyclate and photodynamic therapy with a diode laser had the highest probabilities for ranking first and second, respectively. Publication bias was evident, with fewer than expected studies with small effects. The lack of these studies inflated the treatment effects by an estimated by 20%. Conclusions: Adjuncts improve CAL gain by about a third of a mm over 6–12 months compared with SRP alone, but no significant differences were found among the adjuncts. The patient‐perceived benefit of this gain is unclear because CAL is a physical measure made by the clinician and not a patient‐oriented outcome. Publication bias inflated the observed treatment effects.